HUBUNGAN MALNUTRISI DENGAN KEJADIAN STROKE - Aditya Batlajery; Esdras Ardi Pramudita; Sugianto Sugianto; Rizaldy Taslim Pinzon (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: Stroke is a serious health problem that is characterized by high morbidity and mortality. One of the risk factors for stroke able to be controlled is malnutrition (undernutrition). Malnutrition can be assessed by Total Lymphocyte Count (TLC) if a low TLC value is found or less than 1500 cells/mm3. Undernutrition increases the risk of cerebrovascular disease. Lack of substances such as vitamins can affect brain blood vessels.Objective: To determine the relationship of malnutrition assessed according to the parameter of Total Lymphocyte Count (TLC) to stroke. Methods: This study used a cross-sectional research method. The sample was obtained from the medical record data of the patient in the nerve polyclinic at Bethesda Hospital, Yogyakarta. The sample size in this study was 210 medical records consisting of 105 stroke patients and 105 non-stroke patients. Data from medical records obtained were analyzed by computerization and tested by univariate analysis followed by bivariate analysis with chi-square test. Results: In this study, the description of sex showed that the majority were male patients by 119 (56.7%), while female patients were 91 (43.3%). The most age ranges in this study were aged 60-69 years and over 70 years, each of which was 64 (30.5%). The most common risk factor was hypertension with 131 patients (62.4%). In the statistical analysis it was found that hypertension showed a significant relationship (RP: 4.85, 95% CI: 2.62-8.97, p: 0.000), and it was the strongest variable related to stroke. Statistical malnutrition did not have a significant relationship to the incidence of stroke (Rp. 0.80, 95% CI: 0.32-2.00, p: 0.644).Conclusion: Generally, malnutrition does not show a significant relationship to stroke. Hypertension is an independent risk factor for stroke.